The The Effect of Social Media on Students' School Life in Indonesia - Nafisah, Ainun; Ahmed, Nasheeta Shareen; Balamurugan, Tharani; Gimka, Kushalini; Wijaya, Lourelyn Clarecya (Tecno Scientifica Publisher, 2024)
Social media has emerged as a ubiquitous force in today's society, facilitating global interactions and information exchange across virtual networks. Numerous studies have been conducted to uncover both the positive and negative effects of social media on students and education. This article explores the pervasive influence of social media on students' school lives, focusing on four key factors: motivating students in academic achievement, utilization for academic discussions, accessibility of study materials through social media, and the potential distraction of school assignments. We investigate the effect of students' screen time on social media on these aspects of their educational experience using a quantitative approach. A survey methodology was employed, with data gathered from 67 students in Indonesia. Preliminary results indicate that social media may not have a significant effect on students' school lives. Additionally, students reported experiencing both negative and positive impacts of social media on their academic endeavors.